JAKOŚĆ W MEDYCYNIEElements of lifestyle of patients after heart transplantation - Marcinkowska, Urszula; Barańska-Kosakowska, Anna; Jaworska, Izabela; Ciszewska, Paulina; Kulig, Magdalena; Wojniak, Edyta; Wesołowski, Bartosz; Jośko, Jadwiga (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Aim of the study : The aim of this article was to bring closer the issue of problems of everyday life met by people after heart transplant and to inform, what elements of their lifestyle have changed after transplantation. Materials and methods : The author’s survey was performed among 56 patients aged 20-70 years (87% men and 13% women), who had heart transplantation in years 1992-2009 in Œl¹skie Centrum Chorób Serca (ŒCCS) in Zabrze. Results : 81% modified manner of nutrition (21% altered it radically), 38% resigned from using alcohol and 45% stopped smoking.54% stated that necessity of using medicaments influenced on their everyday life. The most significant changes are noticeable at professional, familial and social relations: 2/3 of respondents is treated by family in another way than before transplantation, over half of them reduced social relations after surgery. Simultaneously 71% of them are involved in voluntary-association activity within Heart Transplant Association. 45% had not returned to work after transplantation. Conclusions : The results confirm that almost all patients have changed their lifestyle, which is the most noticeable in reference to social-work relations. People after transplantation are medically rehabilitated, but the problem is deficiency of social rehabilitation. Patients having transplanted heart rarely take up job again.